Bilateral Piriform sinus fistulas: a case study and review of management options - Deanna Lammers; Ross Campbell; Jorge Davila; Johnna MacCormick (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Piriform sinus fistulas occur due to developmental abnormalities of the third and fourth branchial arches, and almost always occur unilaterally. They generally present as recurrent abscesses in the anterior-inferior neck, with concurrent thyroiditis. They have conventionally been managed with complete removal of the sinus tract, and thyroidectomy if required; however, endoscopic approaches have been increasingly favored. Herein we describe a case of bilateral piriform sinus fistulas, and present a review of the literature concerning their endoscopic management. Case presentation Our patient was determined to have bilateral piriform sinus fistulas based on computer tomography, magnetic resonance imaging and microlaryngoscopy. We performed electrocauterization of the proximal fistula tracts, followed by injection of fibrin sealent. Our patient has not had a recurrence in the ten months since his procedure. There were no complications. Twenty-three articles describing an endoscopic approach to these fistulas were identified through PubMed, and a search through the references of related articles was completed. Conclusion Of one hundred and ninety-five patient cases we reviewed, an endoscopic procedure success rate of 82% and complication rate of 5.6% was determined. Piriform sinus fistulas that occur bilaterally are a rare congenital abnormality of the neck. Endoscopic approaches are an acceptable alternative option to open procedures, with similar success and a lower rate of complications.